Analysis of Collaboration Profiles in The Strengthening Project of Pancasila Student Profile in Primary Schools - Ndari, Maylinda Surya; Sukarno, Sukarno; Karsono, Karsono (Social, Humanities, and Educational Studies (SHES): Conference Series, 2024)
This paper aims to discuss an analysis of collaboration profile through strengthening the Pancasila student profile project which is currently being implemented in primary schools. The method used is descriptive qualitative research with data collection is conducted through observation, interviews, and documentation. In primary schools, the Pancasila Student Profile project is holistically connected to character development through a collaborative approach. Collaborative learning strategies in primary schools further strengthen the Pancasila Student Profile project, emphasizing positive relationships, collective responsibility, and the application of Pancasila values in daily learning practices. The interview findings underscore the significance of collaboration in fostering leadership skills aligned with Pancasila values among primary school students. Assigning leadership responsibilities and evaluating their impact on team dynamics contribute to character development, with observations focusing on changes in social interactions, classroom atmosphere, student motivation, and educational outcomes. In conclusion, the study reveals the integral role of collaboration in achieving the goals of the Pancasila Student Profile Strengthening Project.